Crises, Rumours and Reposts: Journalists’ Social Media Content Gathering and Verification Practices in Breaking News Situations - Backholm, Klas (2017)
Social media (SoMe) platforms provide potentially important information for news journalists during everyday work and in crisis-related contexts. The aims of this study were (a) to map central journalistic challenges and emerging practices related to using SoMe for collecting and validating newsworthy content; and (b) to investigate how practices may contribute to a user-friendly design of a web-based SoMe content validation toolset. Interviews were carried out with 22 journalists from three European countries. Information about journalistic work tasks was also collected during a crisis training scenario (N = 5). Results showed that participants experienced challenges with filtering and estimating trustworthiness of SoMe content. These challenges were especially due to the vast overall amount of information, and the need to monitor several platforms simultaneously. To support improved situational awareness in journalistic work during crises, a user-friendly tool should provide content search results representing several media formats and gathered from a diversity of platforms, presented in easy-to-approach visualizations. The final decision-making about content and source trustworthiness should, however, remain as a manual journalistic task, as the sample would not trust an automated estimation based on tool algorithms.